Interference in dengue virus adsorption and uncoating by carrageenans - Talarico, Laura Beatriz (2007)
This study demonstrated that the λ- and ι-carrageenans, sulfated polysaccharides containing linear chains of galactopyranosyl residues, are potent inhibitors of dengue virus type 2 (DENV-2) and 3 (DENV-3) multiplication in Vero and HepG2 cells, with values of effective concentration 50% from 0.14 to 4.1 μg/ml. This activity was assayed by plaque reduction, virus yield inhibition and antigen expression tests, and was independent of the input multiplicity of infection in the range 0.001-1. The inhibitory action of the λ-carrageenan, an heparan sulfate (HS)-imitative compound, was exerted by a dual interference with virus adsorption and internalization of nucleocapsid into the cytoplasm. Although virus particles may enter the cell when compound was added after DENV-2 adsorption, as shown by intracellular uptake of radiolabeled DENV-2 particles and quantitative RT-PCR, infectious center and virion uncoating assays have shown that carrageenan-treated virions cannot be released from the endosomes. Viral protein synthesis, the first step of macromolecular synthesis after DENV entry to the host cell, was not affected by the carrageenan. Furthermore, no inhibition of virus multiplication was detected when the entry process was bypassed through DENV-2 RNA transfection into the cell. The dual sites of action of an HS-like molecule suggest that, at least in monkey kidney and human hepatic cells, the HS residues in the cell membrane appear to act as mediators for DENV-2 entry, an interesting alternative target for flavivirus therapy.